The Management of Gallstone Disease A Practical and Evidence-Based Approach (Springer International Publishing, 2018)
This book looks at the comprehensive management of all aspects of gallstone disease, from the epidemiology and pathogenesis to the complex management approaches required for some patients. The main emphasis is placed on effective diagnosis and treatment, making extensive use of practical case-based material while reviewing the guidelines in a multi-disciplinary manner. It is an essential read for all clinicians involved in managing patients with gallstone disease.